The Epistemological Dilemma of Translating Otherness - Lee, Tong (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
This article interrogates the interpretive difficulties arising from the encounter with the Other in translation, specifically in the case where the subjectivity of the target text reader is implicated in the discursive constitution of identity in the source text. In contemplating how Anglophone Chinese Singaporean readers could interpret identities in Chinese literary works that invoke a strong sense of Chinese consciousness, I adopt Berman’s binary ethical framework in analysing the negotiation of Self and Other in translation. I posit that a positive ethics will be achieved if Anglophone Chinese readers position themselves as Other in their own language. On the contrary, a negative ethics ensues if the same group of readers embrace their identity as English-speaking Chinese as Self in the process of reading the Sinophone Other in the texts. The two conflicting positions create an epistemological dilemma on the part of the target text reader, thus raising the question of how identities can or should be negotiated in translation in the Singapore context, given that the cultural disposition of Anglophone Chinese readers is brought to bear on their reception of the cultural Other in translation.